Answer:
9
Step-by-step explanation:
second box is nine because it is half of the 3 x 6 part
Answer: 82
Step-by-step explanation:
We simply need to substitute the values for x and y into the equation
Both variables are already given to us, x=9, y=2
8(9)+2+4(2)
72+2+8
82
Answer:
If you're talking about things like Algebra and Geometry, its Geometry
If you're not, can you be more specific ? :D
Answer:
a= -2 and b=3
Step-by-step explanation:
Step 1) Solve the first equation for a:
a + 3b = 7
a + 3b - 3b = 7 - 3b
a + 0 = 7 - 3b
a = 7 - 3b
Step 2) Substitute(7 - 3b) for a in a second equation and solve for b:
2a = b - 7 becomes:
2(7 - 3b) = b-7
(2 multi.7) - (2 multi.3b)= b-7
14 - 6b = b - 7
14 + 7 - 6b + 6b = b + 6b = b + 6b - 7 +7
21 - 0 = 1b + 6b - 0
21=(1 + 6)b
21 = 7b
21
/7 = 7b/7
3 = 7b/7
3 = b
b = 3
Step 3) Substitute 3 for b in the solution to the first equation at the end of Step 1 and calculate a
:
a = 7 - 3b becomes:
a = 7 − (
3 ⋅ 3)
a = 7 −
9
a = −
2
Answer:
425/7
Step-by-step explanation:
I used a calculator. Hope this helped!!